DNA polymerase η contributes to genome-wide lagging strand synthesis. Issue 5 (28th December 2018) - Kreisel, Katrin; Engqvist, Martin K M; Kalm, Josephine; Thompson, Liam J; Boström, Martin; Navarrete, Clara; McDonald, John P; Larsson, Erik; Woodgate, Roger; Clausen, Anders R
Abstract: DNA polymerase η (pol η) is best known for its ability to bypass UV-induced thymine–thymine (T–T) dimers and other bulky DNA lesions, but pol η also has other cellular roles. Here, we present evidence that pol η competes with DNA polymerases α and δ for the synthesis of the lagging strand genome-wide, where it also shows a preference for T–T in the DNA template. Moreover, we found that the C-terminus of pol η, which contains a PCNA-Interacting Protein motif is required for pol η to function in lagging strand synthesis. Finally, we provide evidence that a pol η dependent signature is also found to be lagging strand specific in patients with skin cancer. Taken together, these findings provide insight into the physiological role of DNA synthesis by pol η and have implications for our understanding of how our genome is replicated to avoid mutagenesis, genome instability and cancer.